2019
DOI: 10.1016/j.jdermsci.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Thimerosal induces skin pseudo-allergic reaction via Mas-related G-protein coupled receptor B2

Abstract: Background: Thimerosal has been used as a preservative in many products which may cause contact dermatitis. It is the second most common allergen in positive patch test reactions, though being a clinical irrelevant allergen. Thimerosal-induced contact dermatitis is generally considered to be a delayed-type hypersensitivity reaction, but it is difficult to explain the fact that most patients develop an allergic reaction upon first encounter with thimerosal. Recent studies have demonstrated the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…On the other hand, recent studies on the pathophysiology of ACD have also reported that the production of cytokines and chemokines by MC activation plays a major role in the magnitude of the inflammatory response mediated by CD8 + T cells [ 95 ]. Mrgprb2-KO mice have been reported to have significantly reduced inflammation, including itching in various models of allergic contact dermatitis [ 97 , 98 , 99 ], suggesting that MRGPRX2 is involved in the development of ACD as well as atopic dermatitis.…”
Section: Type 2 Inflammationmentioning
confidence: 99%
“…On the other hand, recent studies on the pathophysiology of ACD have also reported that the production of cytokines and chemokines by MC activation plays a major role in the magnitude of the inflammatory response mediated by CD8 + T cells [ 95 ]. Mrgprb2-KO mice have been reported to have significantly reduced inflammation, including itching in various models of allergic contact dermatitis [ 97 , 98 , 99 ], suggesting that MRGPRX2 is involved in the development of ACD as well as atopic dermatitis.…”
Section: Type 2 Inflammationmentioning
confidence: 99%
“…The relationship between the presence of Thiomersal and a pseudoallergic skin reaction was investigated by Peng et al (2019) [ 42 ]. The study showed that MrgprB2/MRGPRX2 had an effect on Thimerosal-induced mast cell degranulation as well as the pseudoallergic response in mice—thus, it may play an important role in contact dermatitis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…A new connection is being discovered between MRGPRX2 and contact dermatitis. Peng et al discovered that thimerosal, a preservative known for inducing contact dermatitis, is capable of inducing mast cell degranulation and increase of calcium concentration in HEK293 cells transfected with either MRGPRX2 or mrgprb2, and that LAD2 cells with a downregulated receptor showed reduced degranulation when exposed to the agent [72]. Presence of thimerosal induces contact dermatitis in dorsal skin and footpad swelling of mice with a normal receptor, an effect that is attenuated when the receptor is knocked out [72].…”
Section: Skin and Connective Tissue Pathologiesmentioning
confidence: 99%
“…Peng et al discovered that thimerosal, a preservative known for inducing contact dermatitis, is capable of inducing mast cell degranulation and increase of calcium concentration in HEK293 cells transfected with either MRGPRX2 or mrgprb2, and that LAD2 cells with a downregulated receptor showed reduced degranulation when exposed to the agent [ 72 ]. Presence of thimerosal induces contact dermatitis in dorsal skin and footpad swelling of mice with a normal receptor, an effect that is attenuated when the receptor is knocked out [ 72 ]. Interestingly, the receptor seems to mediate both an immediate, non-IgE reaction as well as a delayed hypersensitivity-type reaction in mice, evidence that the receptor has multiple capabilities in distinct types of hypersensitivities.…”
Section: Prolonged Type-2 Inflammationmentioning
confidence: 99%
See 1 more Smart Citation